PENGARUH STRUKTUR MODAL, PROFITABILITAS, GROWTH OPPORTUNITY DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Deli, Eka Putri Ismi Novita; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACT This research is meant to examine (1) the influence of capital structure to the firm value, (2) the influence of probability to the firm value (3) the influence of growth opportunity to the firm value (4) the influence of liquidity influence to firm value.This research is a casual comparative research (causal-comparative research). The research population is manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. The sample has been determined by using purposive sampling and predetermined criteria, so that 18 companies (90 firm year) which have fulfilled criteria have been obtained as samples. The data has been obtained from Indonesian Capital Market Directory (ICMD) and through the STIESIA Surabaya investment gallery Indonesia stock exchange Surabaya. The data analysis technique has been carried out by using classic assumption test, multiple regression and hypothesis test.The result of the research shows that based on the model feasibility the variavles of capital structure, profitability, growth opportunity, and liquidity have been obtained and give significant influence to the firm value, it also shows that the influence of independent variables, can explain the variety of firm value. Meanwhile, the result of hypothesis test has proven that; 1)Capital structure has significant and positive influence to the firm value; 2)Profitability has significant and positive influence to the firm value; 3) Growth opportunity has significant and positive influence to the firm value; 4) Liquidity has significant and positive influence to the firm value Keywords: Capital structure, profitability, growth opportunity, liquidity, firm value